Building Semantic Knowledge Base for the Visual Perception- Cognitive Ability of Neuropsychology Using Web Ontology Language - Karnam Akhil; A. Brahmananda Reddy; Abhinav Borad; Pullagura M. Chandra Mouli; Chalasani Akhil Chowdary (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Cognitive Science deals with the study of the human mind and brain. It focuses on the mechanisms involved in representing and manipulating knowledge and how intellectual graphics and processes are realized in the human brain. A cognitive scientist considers the brain an abstract computing device in which neural tissue carries out mental computations to support cognition. They aim to understand the mental computations that underlie cognitive functioning and how these computations are realized. Several disciplines have converged to form the field of cognitive science, which is composed of various disciplines. Several important factors contribute to the study of cognitive psychology, linguistics, and a portion of computer science and artificial intelligence. However, there are also essential components that can be drawn from neurosciences, philosophy, and anthropology that are useful for understanding these areas. Developing a theoretical framework can be achieved in many ways, one of which is by constructing and testing computational models analogous to mental operations to establish theoretical frameworks. Researchers have developed computational models that simulate aspects of human performance, such as deductive reasoning, concept formation, mental imagery, and similar problem-solving, to complement psychological experiments on these topics. In this Paper, various Concepts of Psychological issues, theories, Visual perception and Sense organs are discussed. Object properties are defined for the different aspects of psychology , using protégé editor, Web Ontology language is used to build Knowledge base.